The Parental Impact on Education: Understanding the Correlation between the Parental Involvement and Academic Results - Claudia; Paun Nicoleta (Sciendo, 2024)
Extensively researched in the realm of education, the involvement of parents in their offspring's academic performance has been the subject of increased attention. This article aims to examine the impact of parental contribution on their children's scholastic accomplishments, concentrating on the statistical correlation between the two.